An enquiry into the living conditions of Tea Garden workers of Bangladesh: a case study of Khan Tea Estate - Rahman, Afrazur (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of MA in Governance and Development, 2016.